Low Cost AIP Design in 5G Flexible Antenna Phase Array System Application - Tung, Wei-Shin (Archīum Ateneo, 2020)
In this paper, a low cost 28 GHz Antenna-in-Package (AIP) for a 5G communication system is designed and investigated. The antenna is implemented on a low-cost FR4 substrate with a phase shift control integrated circuit, AnokiWave phasor integrated circuit (IC). The unit cell where the array antenna and IC are integrated in the same plate constructs a flexible phase array system. Using the AIP unit cell, the desired antenna array can be created, such as 2 × 8, 8 × 8 or 2 × 64 arrays. The study design proposed in this study is a 2 × 2 unit cell structure with dimensions of 18 mm × 14 mm × 0.71 mm. The return loss at a 10 dB bandwidth is 26.5–29.5 GHz while the peak gain of the unit cell achieved 14.4 dBi at 28 GHz.